2011
DOI: 10.1097/dcr.0b013e31822c5398
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Human Acellular Dermal Matrix Plug in Closure of Complex Anal Fistulas With a Single Tract

Abstract: Given the low morbidity and relative simplicity of the procedure, we suggest that an acellular dermal matrix plug is a reasonable option for closure of complex anal fistulas with a single tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
1
31
1
Order By: Relevance
“…[3][4][5] Repair of the skin defect following wide resection of an advanced laryngeal carcinoma always necessitates flap reconstruction. Its use and clinical outcomes are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Repair of the skin defect following wide resection of an advanced laryngeal carcinoma always necessitates flap reconstruction. Its use and clinical outcomes are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that longer tracts have better chances of closure [12]. Results with bioprosthetic plugs have shown higher results varying from 54 % to 72 %, although the test series have been very small [13][14][15].…”
Section: Which Is the Best Surgery For Fistula In Ano?mentioning
confidence: 99%
“…one of the principal causes of treatment failure is plug migration or extrusion, 1,21 which has been reported to occur in 4% to 41% of cases. 20 Plug dislodgment has also been problematic in the 2 studies of other "biological" fistula plugs (ie, devices made of human or porcine acellular dermal matrix) that have been published, with the reported rates being 21% 22 and 11%. 23 Because of these disappointing outcomes, the need remains for an effective, minimally invasive, sphincter-sparing therapy for anal fistulas.…”
mentioning
confidence: 97%